An Innovative Non-Pillar Coal-Mining Technology with Automatically Formed Entry: A Case Study. (November 2020) - Zhang, Xingyu; He, Manchao; Yang, Jun; Wang, Eryu; Zhang, Jiabin; Sun, Yue
Highlights: Innovative approach of non-pillar coal mining is accompanied by the automatically formed entry. The mutual cooperation of three key techniques achieves non-pillar coal mining engineering. A field test verified the feasibility and effectiveness of the non-pillar coal mining technology. The proposed non-pillar coal mining technology is supposed to popularize on a large scale. Abstract: A non-pillar coal-mining technology with an automatically formed entry is proposed, which reduces the waste of coal resources and the underground entry drivage workload. Three key techniques in this technology cooperate to achieve automatic formation and retaining of the gob-side entry, and to realize non-pillar mining. Constant-resistance large deformation (CRLD) support ensures the stability of the entry roof; directional presplitting blasting (DPB) separates the entry roof and the gob roof; and a blocking-gangue support system (BGSS) integrates the caved rock material as an effective entry rib. An industrial test was conducted to verify the engineering effects of these key techniques. The field application results showed that the retained entry was under the pressure-relief zone due to the broken-expansion nature of the caved rock mass within the DPB height. After going through a provisional dynamic pressure-bearing zone, the retained entry entered the stability zone. The final stable entry meets the requirements of safety and production. The research results demonstrate the good engineering applicability of this technology. By taking the framework of the technology design principles into consideration and adjusting the measures according to different site conditions, it is expected that the proposed non-pillar coal-mining technology can be popularized on a large scale.